IMPROVING STORAGE ROOT PROTEIN CONTENT IN SWEET POTATO THROUGH OPEN-MATING POLLINATION - Lestari, Sri Umi; Hapsari, Ricky Indri; Sutoyo, Sutoyo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
A field experiment was conducted at the Research Station of Brawijaya University from April to August 2009. An augmented, randomized complete block design with seven blocks was utilized with seven parental clones as standard treatments and seven half-sib families as augmented treatments. Each block consisted of seven parental clones plus one randomly assigned family of half-sibs. In addition, the first block contained 29 accessions, the 2nd block had 120, the 3rd block had 194, the 4th block had 45, the 5th block had 28, the 6th block had 186, and the 7th block had 108. Ten cuttings of each parental clone was planted in each block, along with a single plant of each accession at a spacing of 75 cm in the row and 100 cm between the rows. There were five improved clones identified with high protein content and high yield. Broad-sense heritability and genetic advance of storage root weight, storage root number, percentage dry matter and protein content were high, whereas vegetative biomass and harvest index were low. The results showed that storage root weight, storage root number, percentage dry matter and protein content could be used as the basis for a crop improvement program in sweet potato. Keywords: broad sense heritability, expected genetic advance, improved clones, high yied, protein content, sweet potato